Caring needs and preparedness of pregnant women with severe hypertension required pregnancy termination: Tassanee Noonart - Noonart, Tassanee; Rataya, Maliwan; Lahukarn, Benjawan; Buddum, Maliwan; Suwanpakdee, Walailak (Princess of Naradhiwas University Journal, 2024)
The purpose of the qualitative descriptive study was to examine the caring needs and preparedness of pregnant women with severe hypertension required pregnancy termination. 15 informants were selected based on the necessary criteria using a purposive sample technique. Data collection used depth individual interviews which were validated by experts. Data was confirmed and verified for accuracy by reflecting the data to informants. The researchers never included personal opinions into any data analysis procedure. The tape record was transcribed to assess and summarize the interview data. The purpose of the research was followed throughout the content analysis and data analysis. The purpose of the conclusion was to address the research question. According to the findings, the three main types of caring needs were: 1) encouraging everyday activities; 2) seeking useful knowledge about the course of the disease and treatment; and 3) seeking immediate medical attention to soothe anxiety and pain. Nearly all the informants said that they were not prepared for the need to terminate a pregnancy when it was necessary, which led to worry and tension about what might happen in the future, particularly if they were preterm labor. A preterm baby was at danger for potentially fatal complications after delivery. To minimize adverse effects, physical and psychological preparedness were crucial. The findings highlight the significance of responding caring needs and preparedness of pregnant women with severe hypertension to improve the quality of their future medical treatment.